Penguatan Pendidikan Karakter di Sekolah Dasar: Studi Implementasi di SD Brawijaya Smart School - Bagus Cahyanto; Adilah Salsabilah Mukhtar; Zilda Ba’da Mawlyda Iliyyun; Faisal Faliyandra (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
The 21st-century skills focus on cognitive aspects and various complex aspects, including character-related ones. The emergence of various phenomena, such as catching up with children, bullying, and several cases of moral degradation in the younger generation, reinforces the importance of strengthening character education, especially at the basic education level. To develop the implementation of character education, many primary education institutions have a program strategy to create a school culture that supports the formation of the character of students. SD Brawijaya Smart School is one of the schools that implements character education at the elementary school level. This study aims to strengthen religious character education in schools, supporting and inhibiting factors. The researcher used an approach with a descriptive type. The results show that to build religious character, schools have done several things, including (a) habituation of reading Asmaul Husna, (b) habituation of disciplined attitudes, (c) habituation of responsibility attitudes, and (d)Qur'an literacy habituation. The supporting factors support the character of the school (a) the support from the parents of students, (b) the commitment of the entire school community, and (c) adequate facilities. In addition, there are inhibiting factors that strengthen the character, including (a) the availability of students' internet networks that are not evenly distributed, (b) limited time for courageous learning, and (c) the need for awareness of students